1997
DOI: 10.1046/j.1469-0705.1997.10020103.x
|View full text |Cite
|
Sign up to set email alerts
|

Echogenic material in the fetal gallbladder and fetal disease

Abstract: The presence of echogenic material within the gallbladder is probably a rare finding in the fetus, and the list of predisposing factors known for postnatal life seems not to be applicable to prenatal diagnosis. In the present study 1656 obstetric scans were performed on referrals to the Unit of Fetal Medicine. No echogenic gallbladder contents were found before 28 weeks. In the subgroup of 523 fetuses who were examined during gestational weeks 28-42, six fetuses were found to have echogenic material in the gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
1
24
1
1
Order By: Relevance
“…Interestingly, although Suma et al reported two cases of fetal gallstones among male neonates, they suggested no gender predominance [2]. Nevertheless, most series, including the present report, found an association with male gender [1,3]. No clear explanation could be suggested regarding this association.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, although Suma et al reported two cases of fetal gallstones among male neonates, they suggested no gender predominance [2]. Nevertheless, most series, including the present report, found an association with male gender [1,3]. No clear explanation could be suggested regarding this association.…”
contrasting
confidence: 77%
“…Kiserud et al [1] established a list of predisposing factors associated with fetal echogenic gallbladder, including congenital malformations such as tetralogy of Fallot, bilateral clubfoot, and gastroschisis, chromosomal abnormalities (trisomy 21, translocation 10; 11) and extra-amniotic hematoma with intrauterine growth restriction. Other studies, on the contrary, found fetal gallstones as a benign, isolated condition [2,3].…”
mentioning
confidence: 99%
“…Kiserud et al reported a list of predisposing factor associated with echogenic fetal gallbladder including chromosomal aberrations, cardiac malformations, gastroshisis and intrauterine growth restriction, influence of prostaglandin and possibly prenatal leukomoid reaction (2). However, in our case, and in those described by others, no common etiological factor was found (2,3,5). The only common factor, in a case in the literature was reported as echogenic foci in the gall bladder as a third trimester phenomenon (3,5,6).…”
Section: Answersupporting
confidence: 53%
“…Although we reported a female fetus with no predisposing factor, greater numbers of cases reported in the literature were male (1-3). However, no clear explanation could be suggested regarding this association (2). We suggested that due to the scarcity of cases found and the fact that underlying etiologicl reasons could not be found, the fetal gender may not be associated with gallstones.…”
Section: Answermentioning
confidence: 83%
See 1 more Smart Citation